Effect of physical training on metabolic and bone profile in weaning rats - Arantes, Luciana Mendonça [UNESP]; Bertolini, Natalia Oliveira [UNESP]; Leme, José Alexandre [UNESP]; do Vale, Bruno Augusto Ribeiro [UNESP]; Luciano, Eliete [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: The practice of moderate-intensity exercise can reduce the risk of infections and improve metabolic aspects of the person. Objective: To investigate the effects of aerobic physical training on endocrine and metabolic aspects, bone and immune systems. Methods: Twenty Wistar rats were divided in two groups: sedentary (SG) and trained group (TG). Training program consisted in swimming, 6 weeks, supporting a workload corresponding to 5% of body weight. At the end of the experiment, were performed counting total and differential leukocyte count and hematocrit. After training period, were analyzed glucose, total protein, triglycerides, cholesterol, liver and muscle samples for the determination of the levels of glycogen, and determination of the tibia length and bone area. All dependent variables were analyzed by one-way analysis of variance (ANOVA) and a significance level of P < 0.05 was used for all comparisons. Results: Hematocrit (%) analyzed showed a significant difference, with higher values ffor TG (54.63 ± 1.41) than for the SG (49.5 ± 1.65). The total leukocyte count was not significantly different, as there was no difference in the differential count. Total cholesterol showed significant decrease in TG (TG = 68.27 ± 13.71 mg/dL; SG = 94.44 ± 28.09), the total protein levels also showed significant reduction (TG = 7.3 ± 0.40 g/dL; SG = 7.74 ± 0.36 g/dL) glucose levels and triglyceride showed no significant differences. The bone length showed significant difference (TG = 40±0.14 mm; SG = 42.10 ± 0.12mm). Tibial area showed a lower value for TG (1.53 ± 0.12cm2) than for SG (1.67 ± 0.18cm2); however, the difference was not statistically significant. Conclusion: It can be concluded that aerobic exercise training is able to produce some unique physiological changes in young rats. There is also the need to prescribe exercises that meet the particular maturational stage of development.
Keywords: Immune system; Metabolic aspects; Physical training